A comprehensive view on the manifestations of aggregate demand and aggregate supply shocks in Greece, Ireland, Italy and Portugal - Ionuț Jianu (Theoretical and Applied Economics, 2016)
The main goal of the paper is to extract the aggregate demand and aggregate supply shocks in Greece, Ireland, Italy and Portugal, as well as to examine the correlation among the two types of shocks. The decomposition of the shocks was achieved by using a structural vector autoregression that analyses the relationship between the evolution of the gross domestic product and inflation in the period 1997 2015. The goal of the paper is to confirm the aggregate demand - aggregate supply model in the above-mentioned economies.
Keywords: E31; E32; E37; 330; demand shocks; supply shocks; European Monetary Union; peripheral countries; SVAR